2021
DOI: 10.1111/are.15116
|View full text |Cite
|
Sign up to set email alerts
|

Pectic hydrolysates in the diet of Nile tilapia ( Oreochromis niloticus ): Performance, nutritional composition, histological parameters, enzymatic activity, hepatic parameters and intestinal contents

Abstract: The objective of the work was to investigate the prebiotic potential of pectic hydrolysates extracted from apple pomace and passion fruit peel, added to the diet of Nile tilapia (Oreochromis niloticus). The biological assay introducing pectic hydrolysates in the diet of Nile tilapia (3.9 ± 0.67 g) lasted 42 days. Five experimental diets were evaluated, one of them a control diet and the others with the addition of pectic hydrolysates (2.5 and 5 g/kg). The fish were fed three times a day until apparent satiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
1
0
0
Order By: Relevance
“…The present study showed that the addition of enzymatic cottonseed protein in the diet increased the length and width of the villi and the thickness of the muscle layer, which was beneficial to the absorption of nutrients. Moreover, other studies have demonstrated similar results in Nile tilapia ( Oreochromis niloticus ) [ 63 ] and channel catfish [ 64 ]. The main reason for these findings may be that small peptides can promote the development of intestinal mucosal structure and enhance the absorption capacity of the intestine [ 65 ].…”
Section: Discussionsupporting
confidence: 62%
“…The present study showed that the addition of enzymatic cottonseed protein in the diet increased the length and width of the villi and the thickness of the muscle layer, which was beneficial to the absorption of nutrients. Moreover, other studies have demonstrated similar results in Nile tilapia ( Oreochromis niloticus ) [ 63 ] and channel catfish [ 64 ]. The main reason for these findings may be that small peptides can promote the development of intestinal mucosal structure and enhance the absorption capacity of the intestine [ 65 ].…”
Section: Discussionsupporting
confidence: 62%